Remembering Emotions in Ego-documents: A Few Insights from Cognitive Psychology and Neuroscience - Švaříčková Slabáková, Radmila (Dějiny – teorie – kritika, 2018)
The aim of this article is to problematize the relationship between emotions and memory in ego-documents. Ego-documents (self-narratives or firsthand accounts), such as memoirs, diaries and autobiographies, have traditionally been considered sources that provide direct access to the emotions of people in the past. However – what happens to emotions between the moment they are experienced and the moment of writing? In this article I seek to find an answer to this question, drawing on the findings of cognitive psychology and neuroscience. I provide an overview of this highly disparate domain of research, focusing particularly on flashbulb memory and the fading affect bias. In the second section, I show that cognitive appraisal theories can be particularly useful for the history of emotions because they deny that emotions are purely physical arousals and consider the reconstructive nature of remembered emotions. Although psychological and neuroscientific research into the relationship between memory and emotions has found little common ground, existing studies have demonstrated that remembered emotions cannot be interpreted as direct, unchanged “mirrors of the soul”. On the other hand, the empirical research carried out in these fields can be inspirational for the history of emotions, which is primarily focused on social practices, schemas and norms, in turning our attention back to real lived experience.